2020
DOI: 10.1016/j.heliyon.2020.e05304
|View full text |Cite
|
Sign up to set email alerts
|

Time-related changes in sex distribution of COVID-19 incidence proportion in Italy

Abstract: Background Variable sex-disaggregated data on Coronavirus disease 2019 (COVID-19) incidence proportion (IP) have been reported in different datasets and studies. Factors explaining the inconsistent distribution of COVID-19 among sexes are still unclear. Objectives This study aimed to analyse time-related variation of sex-disaggregated COVID-19 IP in Italy since March 9 th to May 11 th 2020, and to test its associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Additionally, access to healthcare may influence vaccination willingness. The study of Bianconi et al has discussed the potential role of gender inequalities in the access to healthcare facilities in COVID-19 testing and diagnostics [69]. Investigating similar barriers and inequities in healthcare (facility) access could be of interest during vaccine deployment [68].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, access to healthcare may influence vaccination willingness. The study of Bianconi et al has discussed the potential role of gender inequalities in the access to healthcare facilities in COVID-19 testing and diagnostics [69]. Investigating similar barriers and inequities in healthcare (facility) access could be of interest during vaccine deployment [68].…”
Section: Discussionmentioning
confidence: 99%
“…The result of the test confirms that confirmed male and female cases have different distributions and the number of confirmed cases is significantly higher in males. Bianconi et al (2020) argued that gender inequalities may have influenced either the estimation of COVID-19 cases or the susceptibility to COVID-19 over time. Bianconi et al (2020) observed a time-related changes in sex distribution of COVID-19 cases in Italy as well as declining infection proportion with male-female ratio from 9 March to 11 May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Bianconi et al (2020) argued that gender inequalities may have influenced either the estimation of COVID-19 cases or the susceptibility to COVID-19 over time. Bianconi et al (2020) observed a time-related changes in sex distribution of COVID-19 cases in Italy as well as declining infection proportion with male-female ratio from 9 March to 11 May 2020. However, there is no significant time-related changes in sex distribution of COVID-19 cases in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV2 outbreak has had a significant impact on healthcare services and resource allocation. Accumulating evidence has shown that amongst COVID-19-infected patients, elevated mortality is observed in older patients and those with pre-existing comorbidities, including hypertension, diabetes mellitus, cardiovascular disease, chronic lung disease, and cancer [1][2][3].…”
Section: Introductionmentioning
confidence: 99%